Lunar Eclipse Types Comparison of al-Dur al-Anīq with Astronomical Algorithms (Implications for the Law of Lunar Eclipse Prayers) - Yaqin, Alamul; Azmi, Muhammad Farid (University of Muhammadiyah Sumatera Utara, 2025)
This article aims to examine the accuracy of Astronomical Algorithms and al-Dur al-Anīq lunar eclipse type calculations and their impact on the ruling of lunar eclipse prayer. This qualitative research uses descriptive and comparative approaches. This article uses lunar eclipse data from 2011 – 2050 from Astronomical Algorithms, al-Dur al-Anīq, and NASA, and 3 additional partial lunar eclipses with small umbral magnitude. This study concludes that the determination of the type of lunar eclipse al-Dur al-Anīq is more accurate than Astronomical Algorithms because the average magnitude penumbra and umbra difference is almost the same as NASA and there is no difference type of lunar eclipse with NASA. Meanwhile, Astronomical Algorithms there are differences in types of Lunar Eclipses with NASA on lunar eclipses April 4, 2015 and July 18, 2027. The different types of lunar eclipses above, do not have an impact on the difference of lunar eclipse prayer law on lunar eclipse 2011-2050 because the two eclipses differ in No Lunar Eclipse with Penumbra and Partial with Total, but it happens on lunar eclipse 24 February 2157, 16 June 2421, 22 May 2627, because the different types of lunar eclipses occur between Penumbra and Partial.